Isolation and Characterization of Trichoderma Strains Antagonistic Against Pathogenic Fungi on Orange Crops - Tao, Vu Xuan; Tuan, Tran Van (VNU Journal of Science: Natural Sciences and Technology, 2020)
Agricultural production is greatly influenced by diseases caused by fungi. Penicillium digitatum is a common fungus that causes blue mold in citrus fruits. In addition, Fusarium and Phytophthora species are also recognized as citrus pathogens, involving in root rot and fruit rot. Currently, the use of microbial bioproducts to control fungal pathogens is always prioritized for an organic and sustainable agriculture. Trichoderma species are considered as safe filamentous fungi that antagonize against many fungal plant pathogens. In this study, 10 strains of Trichoderma were isolated and monitored for their antagonistic capacity towards the citrus pathogen P. digitatum . The strains Trichoderma Tr.6, Tr.7 and Tr.8 exhibited inhibitory efficacy of 95-100% against P. digitatum . Additionally, these three strains also strongly suppressed the growth of two other common plant pathogens Fusarium oxysporum and Phytophthora capsici . Based on the morphological characteristics and the sequence analysis of the internal transcribed spacer (ITS) region of rDNA, all three strains Tr.6, Tr.7 and Tr.8 were identified as Trichoderma asperellum . These Trichoderma strains represent promising potentials for applications in the production of bioproducts for the control of pathogenic fungi infecting citrus and other crops.